Improvement of BER performance in the MIMO-OFDMA system for mobile WiMAX system using different equalization algorithm / Nor Azlizan Hussien - Hussien, Nor Azlizan (2014)
Combination of Multiple Input Multiple Output (MIMO) and Orthogonal Frequency Division Multiple Access (OFDMA) is implemented to oeffer the simple and high performance system as to increase channel capacity and serve high data rate.